N-acetylgalactosaminyltransferase activity involved in O-glycosylation of herpes simplex virus type 1 glycoproteins. - Serafini-Cessi, F (1983)
We report on N-acetylgalactosaminyltransferase (UDPacetylgalactosamine--protein acetylgalactosaminyltransferase; EC 2.4.1.41) activity in herpes simplex virus type 1 (HSV-1)-infected BHK and RicR14 cells, a line of ricin-resistant BHK cells defective in N-acetylglucosaminyltransferase I. The enzyme catalyzed the transfer of [14C]N-acetylgalactosamine (GalNAc) from UDP-[14C]GalNAc into HSV glycoproteins, as identified by immunoprecipitation. The sugar was selectively incorporated into the immature forms of herpesvirus glycoproteins pgC, pgD, and gA-pgB, which are known to contain N-linked glycans of the high-mannose type. The high incorporation of [14C]GalNAc into endogenous acceptors of HSV-1-infected RicR14 cells was consistent with the accumulation of immature forms of HSV glycoproteins which occurs in these cells. Mild alkaline borohydride treatment of glycoproteins labeled via GalNAc transferase showed that the transferred GalNAc was O-linked and represented the first sugar added to the peptide backbone.